Ocular outcome and frequency of neurological manifestations in patients with acute posterior multifocal placoid pigment epitheliopathy (APMPPE) - Thomas, Bettina C.; Jacobi, Christian; Korporal-Kuhnke, Mirjam; Wildemann, Brigitte; Mackensen, Friederike (Journal of ophthalmic inflammation and infection, 2012)
Purpose: The purpose of this study was to describe the visual prognosis as well as the frequency and clinical severity of central nervous system involvement in all acute posterior multifocal placoid pigment epitheliopathy (APMPPE) patients of one centre.Methods: A retrospective database review of all patients and a prospective clinical, ophthalmological and neurological follow-up, if possible, were conducted.Results: Eighteen patients with APMPPE were included with a mean follow-up of 17.1 months. Thirteen patients participated in a follow-up exam. Visual acuity improved in 9 of 18 patients to a mean of 0.17 log minimum angle of resolution (MAR) in the worse eye and remained stable in eight patients (mean, 0.03 logMAR). In the majority of patients, the 30° static perimetry improved at follow-up compared to the initial exams. Still, in up to 50 to 60 %, small visual field defects persisted. Overall, 11 patients (61 %) showed neurologic symptoms of varying severity. The most common neurological symptom was headache in nine (50 %) patients. Other symptoms included paraesthesias, psychosis, vertigo, and, as the most severe complication, stroke due to cerebral vasculitis. Fifteen patients were treated with systemic corticosteroids.Conclusions: Visual prognosis is good in patients with APMPPE, but visual field defects may remain. Neurological signs and symptoms, especially headaches, are frequent in APMPPE and should be taken seriously. Adequate investigations including MRI and CSF examination should be initiated in these patients.